New records of ground beetles (Coleoptera: Carabidae) for the fauna of the Republic of Macedonia - Hristovski, Slavcho (Acta entomologica slovenica (Ljubljana), 2007)
First records of 15 ground beetle species (Coleoptera: Carabidae) for the fauna of the Republic of Macedonia are presented. These species are Loricera pilicornis, Tachyta nana, Pterostichus elongatus, Pterostichus quadrifoveolatus, Abax carinatus, Amara convexiuscula, Harpalus modestus, Harpalus metallinus, Ophonus schaubergerianus, Ophonus puncticollis, Stenolophus proximus, Stenolophus skrimshiranus, Oodes helopioides, Demetrias imperialis and Cymindis miliaris. Three genera (Loricera, Tachyta and Oodes) are new to the Macedonian fauna as well.
Keywords: entomologija; favna; hrošči; Makedonija; Republic of Macedonia